Jasmonic Acid Seed Treatment Stimulates Insecticide Detoxification in Brassica juncea L. - Sharma, Anket; Kumar, Vinod; Yuan, Huwei; Kanwar, Mukesh Kumar; Bhardwaj, Renu; Thukral, Ashwani Kumar; Zheng, Bingsong (Frontiers in Plant Science, 2018)
The present study focused on assessing the effects of jasmonic acid (JA) seed treatment on the physiology of Brassica juncea seedlings grown under imidacloprid (IMI) toxicity. It has been observed that IMI application declined the chlorophyll content and growth of seedlings. However, JA seed treatment resulted in the significant recovery of chlorophyll content and seedling growth. Contents of oxidative stress markers like superoxide anion, hydrogen peroxide, and malondialdehyde were enhanced with IMI application, but JA seed treatment significantly reduced their contents. Antioxidative defense system was activated with IMI application which was further triggered after JA seed treatment. Activities of antioxidative enzymes and contents of non-enzymatic antioxidants were enhanced with the application of IMI as well as JA seed treatment. JA seed treatment also regulated the gene expression of various enzymes under IMI stress. These enzymes included respiratory burst oxidase (RBO), Ribulose-1,5-bisphosphate carboxylase/oxygenase (RUBISCO), NADH-ubiquinone oxidoreductase (NADH), carboxylesterase (CXE), chlorophyllase (CHLASE), cytochrome P450 monooxygenase (P450). JA seed treatment up-regulated the expressions of RUBISCO, NADH, CXE, and P450 under IMI toxicity. However, expressions of RBO and CHLASE were down-regulated in seedlings germinated from JA seed treatment and grown in presence of IMI. Seed soaking with JA also resulted in a significant reduction of IMI residues in B. juncea seedlings. The present study concluded that seed soaking with JA could efficiently reduce the IMI toxicity by triggering the IMI detoxification system in intact plants.